ChemInform Abstract: Synthesis of Difluoromethyl Ethers with Difluoromethyltriflate. Issue 30 (4th July 2013) - Fier, Patrick S.; Hartwig, John F.
Abstract A simple method for the difluoromethylation of phenols and thiophenols using a non‐ozone‐depleting reagent is described.